Analysis of Thermal Efficiency of the Honda GK5 Engine Fueled with Young Coconut Waste Bioethanol Using a Thermodynamic Approach - Wahyudi, Retno; Ibrahim, Fauzi; Sembiring, Alexander; Apriyanto, Agus; Murti, Adam Wisnu; Putri, Novia Utami (VOCATECH: Vocational Education and Technology Journal, 2025)
The global energy crisis and increasing awareness of the negative environmental impacts of fossil fuels have driven the development of sustainable alternative energy sources. One promising renewable fuel is bioethanol, especially when produced from agricultural waste such as young coconut waste. This study aims to evaluate the effect of using bioethanol derived from young coconut waste on the thermal efficiency of the Honda GK5 engine through thermodynamic analysis based on the Otto cycle model and verification using experimental data. The research method includes laboratory testing of the Honda GK5 engine with variations in fuel mixtures: E0, E10, E20, and E30. The test results show a significant increase in thermal efficiency up to the E20 mixture, with an experimental efficiency of 31.8% and a theoretical efficiency of 32.0%. This improvement is attributed to the high octane number of bioethanol, which supports more complete combustion. However, at the E30 mixture, a decrease in efficiency is observed due to the lower heating value of bioethanol. The Otto cycle model successfully represents the trend of thermal efficiency with an average deviation of 1–1.5% compared to experimental results. Therefore, bioethanol from young coconut waste proves not only to be environmentally friendly but also capable of enhancing engine energy performance optimally without requiring significant modifications.